The relationship between serum klotho and cognitive performance in a nationally representative sample of US adults - Linghui, Deng; Simin, Yu; Zilong, Zhang; Yuxiao, Li; Shi, Qiu; Birong, Dong (Frontiers in Aging Neuroscience, 2023)
Purpose Aging is the primary risk factor for cognitive decline. Serum klotho, as an anti-aging protein, may be involved in cognitive decline. Thus, we aim to explorer the correlation between serum klotho and cognitive performance among an older adult population in the United States. Methods We performed a cross-sectional study using data from NHANES 2011–2014. Serum klotho was analyzed by ELISA. Cognitive function was measured by Establish a Registry for Alzheimer’s Disease (CERAD) test, Animal Fluency test and Digit Symbol Substitution Test (DSST) score. The relationship between serum klotho and cognition was analyzed by a multivariable regression model. Results A total of 2,171 participants aged 60–79 years were included. Median serum klotho concentration was 851.52 pg./ml (SD = 294.07). We also categorized serum klotho concentrates into quartiles. After fully adjusting pertinent variables, compared to those with lowest klotho levels (206.3–658.4 pg./ml), individuals with highest klotho concentrates (983.3–3,456 pg./ml) had a higher CERAD score [β (95%CI): 0.97 (0.25, 1.69) p = 0.008] and DSST score [β (95%CI): 1.86 (0.25, 3.47), p = 0.024]. Conclusion Our findings indicated that, among the general population of American older adults, serum klotho concentrates may serve as a marker of cognitive health. The benefits of klotho on aging process and neurodegenerative disorders should be paid more attention.